La Violencia Económica: panorama de Derecho Comparado - Cabrillac, Rémy (2016)
This paper explains how the notion of economic duress is understood in different legal regimes of Civil Law and Common Law. This way, the author first addresses the concept of economic duress from a restrictive sense (as a defect of consent) and, later, develops the concept from a wider perspective (taking into account an objective economic imbalance).